2017
DOI: 10.1016/j.econmod.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A green winner's curse? Investor behavior in the market for eco-certified office buildings

Abstract: This paper contributes to the growing literature on the economics of green buildings: by merging auction theory and hedonic regression analysis we investigate the relationship between market concentration and price premiums in the American market for eco-certified real estate assets. Auction theory is used to model price formation where eco-investors may differ in their valuation of assets. Controlling for a large number of features, the empirical results provide evidence of a significant and positive relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Globally, there has been much research seeking to link real estate values with sustainability ratings, but the number of UK studies has been limited. Fuerst et al ( 2015; concluded that there was emerging evidence of price differentiation based on EPC; but whether this is by a 'green' premium partially caused by a shortage of high grade stock (Fuerst et al, 2017) or to an emergence of a 'brown discount' for less good stock (RICS, 2019) is questionable. From the interviews the dominant view of valuers was that "generally 'green' issues do not really arise".…”
Section: Valuation Practicementioning
confidence: 99%
“…Globally, there has been much research seeking to link real estate values with sustainability ratings, but the number of UK studies has been limited. Fuerst et al ( 2015; concluded that there was emerging evidence of price differentiation based on EPC; but whether this is by a 'green' premium partially caused by a shortage of high grade stock (Fuerst et al, 2017) or to an emergence of a 'brown discount' for less good stock (RICS, 2019) is questionable. From the interviews the dominant view of valuers was that "generally 'green' issues do not really arise".…”
Section: Valuation Practicementioning
confidence: 99%
“…Such forms of green certification have indeed been found globally to correlate with a (small) rental price premium (Fuerst & McAllister, 2011a;Wiley, Benefield, & Johnson, 2010) used to support this model (Axon et al, 2012;Fuerst, van de Wetering, & Wyatt, 2013). This willingness to pay is potentially self-fulfilling, with the most recent meta-analysis of US data (Fuerst, Gabrieli, & McAllister, 2017) finding that 'eco-investors' pay the most for environmentally certified properties. It might also be self-correcting, as its mainstreaming reduces the differentiation value (Chegut, Eichholtz, & Kok, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Investment decisions and rental deals both constitute and reflect 'the market' created through the qualculative processes described above. Tracing the 'impact' of various green certifications, assessments and regulations as 'price signals' in a classical market is an established area of literature (Chegut et al, 2013;Fuerst & McAllister, 2011;Fuerst & van de Wetering, 2015;Fuerst et al, 2013Fuerst et al, , 2017, which fails to capture fully the recursive effects of their use, along with less formal 'standards', in the creation of a market itself through calculations and deals (MacKenzie et al, 2007). Seeing decisions to invest in energy-efficient buildings as being solely incentivized by their market value premium (De Jong & Parkinson, 2013) ignores: the powerful social processes shaping energy-related decisions which tend to lead development actors to make seemingly 'irrational' choices, building and buying energy-intensive offices beyond the 'needs' of actual occupiers.…”
Section: Discussionmentioning
confidence: 99%
“…Wadu Mesthrige and Chan [15] looked at prime commercial office buildings in Hong Kong used a hedonic-model of rent and building attributes. A US study conducted in 2018 by Fuerst et al [33] also used a hedonic model. They looked at the price investors paid in sealed bid auctions for foreclosed commercial real estate.…”
Section: Financial Factorsmentioning
confidence: 99%